Bonded Labour in Pakistan - Edited by Ayaz Qureshi and Ali Khan (Karachi Oxford University Press, 2016)
The book brings together fresh ethnographic studies with some seminal work that has already been published. In doing so, the volume traverses the macro and micro scales of the study of bonded labour in Pakistan
Include Index
Keywords: Peonage -- Pakistan -- Forced labor